Development of a Bioinspired Soft Robotic System for Teleoperated Endoscopic Surgery - Kefan Zhu; Chi Cong Nguyen; Bibhu Sharma; Phuoc Thien Phan; Trung Thien Hoang; James Davies; Adrienne Ji; Emanuele Nicotra; Jingjing Wan; Patrick Pruscino; Sumeet Walia; Tat Thang Vo-Doan; et al. (Cyborg and Bionic Systems)
Endoscopic submucosal dissection (ESD) has emerged as a critical alternative to laparoscopic excisional surgery for the removal of early gastrointestinal tumors. However, current robotic systems for ESD face challenges with accessibility, dexterity, and precision in confined spaces due to limitations in actuation methods and mechanical design. To overcome these issues, a new motorless, master–slave soft robotic system using hydraulic actuation is introduced for ESD procedures. This system features dual soft robotic arms: one serves as an electrosurgical tool, and the other serves as a 3-jaw soft tubular grasper. Notably, the entire system is powered purely by hydraulic force, eliminating the need for DC motors or complex electronic controllers. Inspired by nature, the grasper ensures even force distribution and removes rotational motion, reducing the risk of iatrogenic injury. Its scalable design and compliant properties allow for effective tissue manipulation in tight spaces, with strong pulling forces generated by the embedded soft actuation network. In vitro and ex vivo experiments on fresh porcine tissues demonstrate the system’s ability to grip and perform electrosurgical cutting on simulated lesions. This innovation has the potential to be applied in other areas of endoscopic surgery as well.